Strategies to Improve Competitiveness at Nusantara 1 and 2 Passenger Terminals through Enhanced Service Facilities - Ginting, Every R Putrita; Rachmadani, Andi Intan; Maulana, Syahrul; Riandika, Syafiq; Maruf, Maruf (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Tanjung Priok Port is one of Indonesia’s largest and busiest ports, playing a vital role in goods trade and passenger transportation. This research focuses on enhancing the infrastructure at the Nusantara 1 and 2 passenger terminals to increase the port’s competitiveness and value, particularly in the passenger terminal area. Using GAP Analysis, literature review, interviews, observations, and documentation, the study aims to provide solutions for improving and expanding passenger terminal facilities to enhance passenger service and value. The findings indicate that optimal maintenance of port infrastructure significantly enhances the port’s value and passenger comfort. Observations reveal a yearly increase in passengers at the PURA 1 & 2 terminals, reaching 353,005 passengers in 2022. The temporary waiting room accommodates 1,600 passengers, while the general waiting room holds 3,666 passengers. Despite the good maintenance of these facilities, further improvements are necessary to meet the growing demands.